DESENVOLVIMENTO DE APLICATIVO PARA ENSINO DO PROCESSO DE ENFERMAGEM EM PEDIATRIA - Nunes, Kelryanna Almeida da Cruz (2020)
Introduction: The nursing process in caring for children and their families in hospital helps to solve real or potential problems, to reduce risks and damages that may arise from hospital care. Thus, it is important to invest in the development of educati